1992
DOI: 10.1007/bf00204008
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the ?-? phase transitions in quartz and cristobalite as observed by in-situ high temperature 29Si and 17O NMR

Abstract: Abstract. Relaxation times (T1) and lineshapes were examined as a function of temperature through the c~-// transition for z9si in a single crystal of amethyst, and for 29Si and 170 in cristobalite powders. For single crystal quartz, the three z9Si peaks observed at room temperature, representing each of the three differently oriented SiO, tetrahedra in the unit cell, coalesce with increasing temperature such that at the c~-//transition only one peak is observed. 29Si Tl's decrease with increasing temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
95
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(103 citation statements)
references
References 57 publications
7
95
1
Order By: Relevance
“…This observation agrees with studies on synthetic cristobalite (e.g. Leadbetter & Wright, 1976;Swainson et al, 2003;Schmahl et al, 1992;Spearing et al, 1992), whereby a smooth change in the intensity of these modes is observed as the proportion of cristobalite existing as either or varies with temperature (x1.2). The coexistence interval is larger in volcanic samples than has been observed for synthetic samples; two potentially complementary factors could contribute to the observed coexistence interval (x1.2): cation substitution and crystallite size.…”
Section: Coexistence Of a And B Phasessupporting
confidence: 91%
See 1 more Smart Citation
“…This observation agrees with studies on synthetic cristobalite (e.g. Leadbetter & Wright, 1976;Swainson et al, 2003;Schmahl et al, 1992;Spearing et al, 1992), whereby a smooth change in the intensity of these modes is observed as the proportion of cristobalite existing as either or varies with temperature (x1.2). The coexistence interval is larger in volcanic samples than has been observed for synthetic samples; two potentially complementary factors could contribute to the observed coexistence interval (x1.2): cation substitution and crystallite size.…”
Section: Coexistence Of a And B Phasessupporting
confidence: 91%
“…Furthermore, a proportion of grains may persist metastably after they have passed their transition temperature. Consequently, at a given temperature within the transitional range, and forms coexist both stably and metastably (Leadbetter & Wright, 1976;Swainson et al, 2003;Schmahl et al, 1992;Spearing et al, 1992). The -transition has been shown to depend on temperature, but not on time, demonstrating that the finite width of the transition range is not simply a kinetic effect (Schmahl, 1993;Leadbetter & Wright, 1976).…”
Section: The A-b Phase Transition In Synthetic Cristobalitementioning
confidence: 99%
“…Some very long longitudinal relaxation times have been reported for 29 Si [10,13,15] and the CPMG-MAS technique may provide a valuable tool in this context as well because sensitivity enhancement by an order of magnitude may turn into a reduction of experiment time of several days. Previously the QCPMG-MAS approach has been applied to lineshapes being several kHz broad but in case of spin-1/2 nuclei the isotropic line width is in the range of 100's of Hz and therefore the separation of the spin-echo sidebands have to be adjusted such that 1=s a is smaller than the linewidth.…”
Section: Resultsmentioning
confidence: 99%
“…Castex and Madon 1995; Fig. 4a-c Comparison of calculated isobaric heat capacity (a) and molar volume (b,c) of brucite with measured data Spearing et al 1992). 298.15 K in Eq.…”
Section: Application To Quartzmentioning
confidence: 99%